What is the value of \( 3 a b+5 b-6 \) when \( a=-1 \) and \( b=3 \) ?
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To find the value of the expression \( 3 a b + 5 b - 6 \) when \( a = -1 \) and \( b = 3 \), we can substitute the values of \( a \) and \( b \) into the expression. First, calculate \( 3 a b \): \[ 3 (-1)(3) = -9 \] Next, calculate \( 5 b \): \[ 5(3) = 15 \] Now, substitute these values into the expression: \[ -9 + 15 - 6 \] Combine the terms: \[ -9 + 15 = 6 \] \[ 6 - 6 = 0 \] Thus, the value of the expression \( 3 a b + 5 b - 6 \) when \( a = -1 \) and \( b = 3 \) is \( 0 \).